A Corpus-based Analysis of Rhetorical Moves and P-frames in an Omani Learner Corpus of Research Project Abstracts - Priya Mathew; Lee Mccallum (National Research University Higher School of Economics, 2024)
Background: Rhetorical moves have long been studied in several disciplinary texts, including research articles and their part-genres. A solid base of literature has emerged in this respect, informing current writing pedagogy for novice writers. However, one part-genre which has been rarely studied is student project abstracts. This paper represents one of the first studies to explore the extent rhetorical moves are realised through the linguistic unit of phrase frames (p-frames) in final year Capstone project abstracts. Methods: Using two faculty-informed analytical frameworks, the paper explores the use of rhetorical moves and p-frames in corpora of Social and Physical Science student abstracts.  The moves and the p-frames (if any) used to realise them were identified in order to understand how students organised this part-genre and to gauge their formulaicity. Results: Amongst the key findings was that Omani students did not perform all the rhetorical moves recommended by the faculty. Moreover, they added spontaneous moves of their own to the abstracts. When performing rhetorical moves, they used very few p-frames, indicating that their approach did not rely on formulaic language of this nature. Conclusions: Pedagogical implications for the Omani context and for broader EAP contexts are discussed.